Occupational Radiation Protection during the Decommissioning of Nuclear Installations Main Aspects of Management, Planning and Conduct. - IAEA (IAEA-TECDOC., 2021)
"This publication presents practical information on occupational radiation protection and examples with good practices from the nuclear industry on how to comply with the requirements established in IAEA Safety Standards Series No. GSR Part 3, Radiation Protection and Safety of Radiation Sources: International Basic Safety Standards, within the context of decommissioning activities. This publication can be used in the planning of new decommissioning projects and for improvements in the implementation of existing decommissioning projects. Useful input for licensing and supervision of decommissioning projects are also provided."